Study of aldehydes, Co and characterization of particles resulting from oil contamination of aircraft bleed air - Nayyeri Amiri, Shahin (Kansas State University, 2018)
Contamination of aircraft bleed air with engine oil and/or hydraulic fluid results in a “fume event” in the aircraft cabin. Exposure to contaminated bleed air may have acute and/or chronic adverse health effects based on the intensity of various chemicals which are released during such a fume event. ASHRAE Standard 161, Air Quality within Commercial Aircraft, includes a requirement for bleed air sensors to detect contamination from lubricating oil. One potential approach to meeting this requirement is through particle detection. In the research reported here, the end goal is to provide data needed to develop an automated detection apparatus for contaminated bleed air through oil particle detection. Consequently, the type and concentration of different chemicals as well as the number and size distribution of particles were determined for bleed air with different rates of contamination under various turbine engine operating conditions. Multiple fume events were simulated by using a four-part experimental program to develop a detailed characterization of particles that result when bleed air is contaminated with lubricating oil. Test results show that oil contamination in the compressor will result in a fog of very fine droplets in the bleed air under most operating conditions. With moderately high contamination rates at elevated power levels (high bleed air temperature) the concentration distribution and particle size does not vary much with power (temperature) and generally depends on the rate of contamination. Moreover, at elevated power levels, the peak particle concentration takes place in the range of 50 to 70 nanometers and the bulk of the particles form at less than 150 nanometers. At very low contamination rates very ultrafine particles can be generated in the size of 10 nanometers or less. As a result, detection is needed for a range of sizes ranging from about 100 nanometers to 10 nanometers.
Keywords: CO; Characterization of particles; aircraft bleed airAldehydes